PROTOTIPE APLIKASI SMART LIGHTING UNTUK MENGONTROL LAMPU JALAN BERBASIS ANDROID MENGGUNAKAN ESP32 - Youzy Natasya; Handri Santoso (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Lighting is essential in life as it provides a sense of security, especially when it comes to street lighting at night. However, negligence often leads to streetlights not functioning in dark conditions. The development of technology, particularly in the field of Internet of Things (IoT), enables devices to interact and exchange data through the internet network. Therefore, IoT technology has been developed to control streetlights remotely using a mobile application. This mobile application consists of three features for controlling the lights. First is the manual control, where users can adjust the intensity of the light emitted by the lamp. Second is the scheduled-based control, allowing users to set specific times for the lamp to turn on and off. Lastly, automatic control, which adjusts the lamp based on the ambient light conditions in the area. The prototype is implemented by designing an IoT system using the WiFi module on the ESP32 mictocontroller, LED lights, and an LDR sensor to measure light intensity. Additionally, a mobile application is developed to control the streetlights. Testing is conducted by controlling the lamps through the built application and gathering feedback through questionnaires to evaluate the usability of the appication’s interfaces. Based on the test results, the application effectively functions to control the streetlights according to the available features, and the application’s interface is user-friendly.